2021
DOI: 10.1002/lpor.202000563
|View full text |Cite
|
Sign up to set email alerts
|

Wavepacket Self‐Rotation and Helical Zitterbewegung in Symmetry‐Broken Honeycomb Lattices

Abstract: The toolbox quantities used for manipulating the flow of light include typically amplitude, phase, and polarization. Pseudospins, such as those arising from valley degrees of freedom in photonic structures, have recently emerged as an excellent candidate for this toolbox, in parallel with rapid development of spintronics and valleytronics in condensed-matter physics. Here, by employing symmetry-broken honeycomb photonic lattices, valley-dependent wavepacket self-rotation manifested in spiraling intensity patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The proposed phenomena, however, could be readily realized in photonic and nanomechanical metamaterials. In photonic crystals the pseudo-electric fields can be created by the site-to-site laser writing [50]. The second extremely promising experimental playground is the platform of "nanomechanical graphene"-a honeycomb lattice of free-standing Si 3 N 4 nanomechanical membranes with a modified lattice structure [51].…”
Section: Resultsmentioning
confidence: 99%
“…The proposed phenomena, however, could be readily realized in photonic and nanomechanical metamaterials. In photonic crystals the pseudo-electric fields can be created by the site-to-site laser writing [50]. The second extremely promising experimental playground is the platform of "nanomechanical graphene"-a honeycomb lattice of free-standing Si 3 N 4 nanomechanical membranes with a modified lattice structure [51].…”
Section: Resultsmentioning
confidence: 99%
“…In most previous studies, optical vortices were typically generated with spatial light modulators, q-plates, metasurfaces, or active vortex generators. On the other hand, a Dirac point in the momentum space similar to that displayed by graphene can be considered a topological singularity (TS) with nontrivial Berry phase winding. In recent experiments, it has been demonstrated that optical vortices can be generated by mapping the TSs from momentum to real space using photonic structures. This brings about a new way for the generation, manipulation, and transformation of optical vortex beams, along with new features mediated by pseudospin-to-OAM conversion. ,,,, …”
mentioning
confidence: 99%
“…In photonics, waveguide arrays are arranged to form HCLs, namely, photonic graphene, where light propagation can mimic electronic transport properties in graphene. Based on such photonic graphene lattices, we have observed several intriguing phenomena in a series of experiments, including unconventional edge states, valley Landau–Zener–Bloch oscillations, valley-dependent vortex states, and wavepacket self-rotation, in addition to pseudospin angular momentum . In particular, under proper alignment of the pseudospin states near the Dirac points, optical vortices of different topological charges can be generated via momentum-to-real-space TS mapping .…”
mentioning
confidence: 99%